Extent of weight reduction necessary for minimization of diabetes risk in Japanese men with visceral fat accumulation and glycated hemoglobin of 5.6–6.4%. Issue 5 (15th March 2015) - Iwahashi, Hiromi; Noguchi, Midori; Okauchi, Yukiyoshi; Morita, Sachiko; Imagawa, Akihisa; Shimomura, Iichiro
Abstract Aims/Introduction Weight reduction improves glycemic control in obese men with glycated hemoglobin (HbA1c) of 5.6–6.4%, suggesting that it can prevent the development of diabetes in these patients. The aim of the present study was to quantify the amount of weight reduction necessary for minimization of diabetes risk in Japanese men with visceral fat accumulation. Materials and Methods The study participants were 482 men with an estimated visceral fat area of ≥100 cm2, HbA1c of 5.6–6.4%, fasting plasma glucose (FPG) of <126 mg/dL or casual plasma glucose <200 mg/dL. They were divided into two groups based on weight change at the end of the 3‐year follow‐up period (weight gain and weight loss groups). The weight loss group was classified into quartile subgroups (lowest group, 0 to <1.2%: second lowest group, ≥1.2 to <2.5%: second highest group, ≥2.5 to <4.3%: highest group, ≥4.3% weight loss). The development of diabetes at the end‐point represented a rise in HbA1c to ≥6.5% or FPG ≥126 mg/dL, or casual plasma glucose ≥200 mg/dL. Results The cumulative incidence of diabetes at the end of the 3‐year follow‐up period was 16.2% in the weight gain group and 10.1% in the weight loss group (P not significant). The incidence of diabetes was significantly lower in the highest weight loss group (3.1%), but not in the second highest, the second lowest and the lowest weight loss groups (9.7, 10.1 and 18.3%), compared with the weight gain group. Conclusions Minimization of the risk of diabetes in Japanese men with visceral fat accumulation requires a minimum of 4–5% weight loss in those with HbA1c of 5.6–6.4%.